Penentu Kualitas Audit dan Peran Moderasi Komite Audit - Normasyhuri, Khavid; Natalelawati, Ignasia (E-Jurnal Akuntansi, 2022)
Quality audits have an impact on the quality of good financial reports. This study aims to examine the factors that affect audit quality and see that the audit committee is able to strengthen or weaken audit quality. The research sample is manufacturing companies listed on the IDX from 2019-2021. Sampling is done by purposive sampling technique. Data analysis used logistic regression and Moderate Regression Analysis (MRA). The results of the Audit Tenure research have a negative effect on audit quality, the reputation of the Public Accounting Firm (KAP) and audit fees have a positive effect on audit quality, the audit committee weakens the influence of audit tenure on audit quality. Meanwhile, the audit committee strengthens the influence of KAP reputation and audit fees on audit quality. Keywords: Tenure Audit; KAP Reputation; Audit Fees; Audit Quality; Audit Committee.